2018
DOI: 10.1016/j.bbadis.2017.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Activin-A causes Hepatic stellate cell activation via the induction of TNFα and TGFβ in Kupffer cells

Abstract: Activin-A may induce fibrosis in NASH and alcoholic cirrhosis via activation of KCs to express pro-inflammatory molecules that promote HSC-dependent fibrogenesis and could be a target for future anti-fibrotic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 43 publications
0
36
1
Order By: Relevance
“…A number of intraand extracellular inhibitors, including follistatin and follistatin-related proteins that bind and disable activin-A, coordinate its effects. [31][32][33][34][35] One well established effects of activin-A is it´s role in the wound cure and fracture consolidation. Deregulation of this process is related to pathological collagen accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of intraand extracellular inhibitors, including follistatin and follistatin-related proteins that bind and disable activin-A, coordinate its effects. [31][32][33][34][35] One well established effects of activin-A is it´s role in the wound cure and fracture consolidation. Deregulation of this process is related to pathological collagen accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models and small series of patients suggest that activin-A system can participate in inflammation and liver fibrosis. 20,[31][32][33][34] Oxidative stress is also responsible for production of proinflammatory cytokines, among which stand out: TNF-α, transforming growth factor alpha and beta (TGF-α and TGF-β), interleukin-6 (IL-6), interleukin-8 (IL-8), NFκB and adiponectin. These cytokines are produced by lymphocytes and Kupffer cells, mediated by free radicals and it may act by changing the mitochondrial membrane permeability and inhibiting the respiratory chain 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated HSCs secrete an extracellular matrix, mainly collagen I, III, and IV [ 71 , 72 ]. Overall, induction of TNF- α and TGF- β in Kupffer cells leads to HSC activation resulting in an upregulation of fibrosis markers α -SMA and col-1 α [ 73 ]. Studies have reported reversal of liver injury via regulation of proinflammatory genes by medicinal plants such as Aspalathus linearis [ 68 ] and Cynara scolymus L. [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the studies showed that α-SMA was a marker of the initiation stage of HSCs activation, which was evidently raised in the liver region of bridging fibrosis, and the mRNA levels of hepatic col1α1 and col1α2, markers for the perpetuation stage of HSCs activation, were clearly elevated in fibrotic mice ( Osterreicher et al, 2009 ; Wang et al, 2013 ; Heindryckx et al, 2016 ). Several reports demonstrated that inflammatory cytokines such as MCP1, IL-1β, IL-6, and TGF-β1 were closely related to the activation of HSCs ( Moles et al, 2014 ; Wu et al, 2015 ; Kim et al, 2017 ; Kiagiadaki et al, 2018 ). It was reported that pre-treatment with IRE1α inhibitor reduced pro-inflammatory cytokines production in tumor necrosis factor (TNF)-receptor-associated periodic fever syndrome (TRAPS) dermal fibroblasts (DFs) ( Harrison et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%